Transportation Problem Optimization Systems using The Algorithm of Allocation Table Method - Wahyu Sri Utami; Saucha Diwandari; Aditya Hermawan (International Journal of Applied Business and Information Systems, 2019)
Transportation is the process of distributing products from source to destination. Transportation problems are special cases of network optimization method where the numbers of goods distributed from sources to destinations are optimized thereby minimizing transportation costs. The increasing number of sources and destinations results in complex calculations of the distribution process. The methods to find optimal solutions in determining the number of goods distributed with the aim of minimizing costs have been proposed. Comparative methods have been carried out and obtain optimal solutions. The result shows that the algorithm of the Allocation Table Method has shown better performance compared to previous methods such as Least Cost Method, Vogel Approximation Method dan North West Corner Method. Yet, a more complex transportation network needs a calculation method to seek for solutions. The aim of the study was to implement the algorithm of the Allocation Table Method as a method to seek solutions in a system designed to support problem-solving. The tryout conducted on several cases has shown that the Allocation Table Method is a leading method in finding optimal solutions for transportation problems involving multi-sources and multi destinations.